Associations of traffic noise with self-rated health and psychotropic medication use - Jaana I Halonen; Timo Lanki; Tarja Yli-Tuomi; Anu W Turunen; Jaana Pentti; Mika Kivimäki; Jussi Vahtera (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: Road traffic noise is a common environmental nuisance, which has been thought to increase the risk of many types of health problems. However, population-level evidence often remains scarce. This study examined whether road traffic noise is associated with self-rated health and use of psychotropic medication in a cohort of public sector employees. METHODS: Data are from the Finnish Public Sector Study cohort. Geographical information system (GIS) was used to link modeled outdoor road traffic noise levels (L_den) to residential addresses of 15 611 men and women with cross-sectional survey responses on self-rated health and register-based information on the use of antidepressants, anxiolytics, and hypnotics. High trait anxiety scores were used to identify potentially vulnerable individuals. The analyses were run with logistic regression models adjusting for individual and area-level variables. All participants were blind to the aim of the study. Results Mean level of road traffic noise at participants' home addresses was 52 decibels (dB) (standard deviation 8.1). Noise level >60 dB versus ≤45 dB was associated with poor self-rated health in men [odds ratio (OR) 1.58, 95% confidence interval (95% CI) 1.14-2.21]. Further stratification revealed that the association was evident only among men with high trait anxiety scores (OR 2.23, 95% CI 1.28-3.89). No association was found with psychotropic medication use or among women. CONCLUSION: Exposure to road traffic noise was not associated with increased use of psychotropic medication, although it was associated with weakened self-rated health among men.